2017
DOI: 10.11646/phytotaxa.307.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic analysis for elucidating the taxonomic position of selected unicellular marine cyanobacteria from Indian and Hong Kong coast

Abstract: Cyanobacteria, the primordial oxygenic photosynthetic prokaryotes encompass a wide spectrum of morphologies and ecologies. The diversity of twelve marine unicellular cyanobacteria isolated from different marine habitats was analyzed morphologically. The evolutionary relationship among the investigated strains was examined by phylogenetic analysis of nearly complete 16S rRNA gene and 16-23S internal transcribed spacer region. Phylogenetic analysis of both 16S rRNA genes and internal spacer regions exhibited coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…BDU 130052 (Bhuvaneshwari et al. 2017). However, to the best of our knowledge, none of latter strains were formally described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BDU 130052 (Bhuvaneshwari et al. 2017). However, to the best of our knowledge, none of latter strains were formally described.…”
Section: Discussionmentioning
confidence: 99%
“…S1) also showed that Petrachloros forms a cluster with environmental sequences isolated during the studies of Couradeau et al (2011), and Sahl et al (2010 and a GenBank 16S rRNA gene sequence identified as Aphanocapsa sp. BDU 130052 (Bhuvaneshwari et al 2017). However, to the best of our knowledge, none of latter strains were formally described.…”
Section: Cyanobium Gracilementioning
confidence: 96%
See 1 more Smart Citation